The Challenges of the Bioclimatic Architecture in Romania. Issue 3 (December 2020) - Gherghescu, Dragoş-Ştefan; Dabija, Ana-Maria
Abstract: The Bioclimatic Architecture is an architectural style, new as terminology in the history of architecture, but old in its principles, that can be found in the history of the vernacular architecture since the first types of houses appeared. Nowadays, due to the need of eco-friendly ways of building and due to the need of green energy consumption, it emerged in different architectural styles aiming to develop the built space in different manners. Green, Passive, Solar and Bioclimatic Architecture. Each one of them is depending on the natural factors, but from all of them, Bioclimatic Architecture uses all the natural resources available on the site through the volume of the construction in passive ways, sing reduced amounts of energy. First bioclimatic models appeared in hot climate, where they successfully responded to the only needs of cooling the interior air by solar protection and by natural ventilation, and also using the thermal inertia for providing warm air during the cold summer nights. The main problem appears in the temperate zone where, during the winter time, the need of active systems for providing higher indoor temperature appears a warm indoor temperature against the sub-zero outside temperature. This paper aims to highlight the particularities of Romanian continental climate that influences the bioclimatic model, to mark the limit where the passive bioclimatic principles stop, and from where the active systems begin.